ASUHAN KEPERWATAN PADA Ny. D DENGAN CKD (Chronic Kidney Disese) YANG MENJALANI HEMODIALISIS DI RUANGAN PEJUANG RSUD BANGKINANG TAHUN 2025 - Tetti; Riani (Jurnal Spektrum Kesehatan Indonesia, 2025)
Chronic Kidney Disease (CKD) is a major health problem characterized by a progressive decline in kidney function lasting more than three months. Based on data from 2024 and 2025, CKD ranked 10th among the ten most prevalent diseases at RSUD Bangkinang. The causes of CKD are varied, including diabetes mellitus, hypertension, infections, urinary tract obstructions, immune disorders, and congenital diseases that lead to decreased GFR. This study aims to implement nursing care for CKD patients undergoing hemodialysis at RSUD Bangkinang, specifically for Mrs. D, who was treated in the Pejuang ward. Data collection methods included direct observation, interviews with patients and families, and medical record documentation review. The nursing care process was carried out through five stages: assessment, establishing nursing diagnoses, planning interventions, implementing nursing actions, and evaluating outcomes. The researcher identified four main nursing problems: Ineffective Breathing Pattern, Hypervolemia, Acute Pain, and Impaired Skin/Tissue Integrity. Nursing interventions were implemented according to the care plan, including airway management, fluid management, pain management, and skin integrity care. The conclusion of this case study indicates that nursing care for CKD patients undergoing hemodialysis requires a holistic, collaborative, and continuous approach to improve patients’ quality of life.